Modulation of Pro- and Antifibrinolytic Properties of Human Peritoneal Mesothelial Cells by Transforming Growth Factor β1 (TGF- β1), Tumor Necrosis Factor α (TNF-α) and Interleukin β1 (IL-1β) - Tietze, Lothar; Elbrecht, Anne; Schauerte, Carsten; Klosterhalfen, Bernd; Amo-Takyi, Baffour; Gehlen, Johanna; Winkeltau, Gerd; Mittermayer, Christian; Handt, Stefan (Thrombosis and Haemostasis, 1998)
A decreased fibrinolytic activity of serosal surfaces appears to be a major factor in the development of peritoneal fibrous adhesions. Serosal fibrinolysis is regulated by mesothelial release of tissue type plasminogen activator (t-PA) and plasminogen activator inhibitor types 1 and 2 (PAI-1 and PAI-2). We investigated the influence of tumor necrosis factor alpha (TNF-α), transforming growth factor β (TGF- β1) and interleukin 1β (IL-1β) on pro- and antifibrinolytic properties of mesothelial cells (HOMC) using a cell/fibrin clot assay. TGF-β1, TNF-α and IL-1β induced a dose dependent 2.9, 2.3 and 1.9-fold increase of PAI-1 antigen, respectively, whereas t-PA concentrations decreased to one third of the control values. This modified PAI-1/t-PA secretion pattern leads to a significant delay of fibrinolysis. Analysis of m-RNA levels revealed increased PAI-1 m-RNA concentrations after 12 h and decreased m-RNA concentrations for t-PA after 6 h. Serosal hypofibrinolysis during peritonitis may be explained at least in part by cytokine effects which thus may favor adhesion formation.